The Role of Platelet-Rich Fibrin in Increasing the Gingival Thickness and Modifying the Thin Gingival Biotype: A Comparative Clinical Split Mouth Study - Suleiman Dayoub; Mueataz Al-Qershi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Thin gingival biotype (GBT) is of clinical relevance in orthodontic and periodontic treatment, so thick biotype is a requisite for good periodontal health. The aim of this study was to evaluate the effectiveness of platelet-rich fibrin (PRF) with tunnel flap compared to connective tissue graft (CTG) with tunnel flap in increasing gingival thickness (GTH). Material and Methods: Twenty orthodontic patients presenting thin GBTs were included in this study. Treatment sites were divided into test group (PRF) and control group (CTG). Clinical parameters as GTH, GBT, and width of keratinized gingiva (WKG) were assessed at baseline and 6 months post-surgically. Statistical analysis was performed using independent T-test for intergroup comparison. Statistical significance was set at 0.05. Results: The mean GTH at 6 months was 1.57 mm for test group and 1.64 mm for control group. The gain of WKG was 1.57 and 2.08 mm in test and control sites, respectively. Conclusion: Within the limits of this study, using PRF in modifying thin GBT is a successful treatment option and could serve as an alternative to connective tissue grafts (CTGs).